2010
DOI: 10.1051/0004-6361/201014090
|View full text |Cite
|
Sign up to set email alerts
|

CS, HC3N, and CH3CCH multi-line analyses toward starburst galaxies

Abstract: Aims. We aim to study the properties of the dense molecular gas towards the inner few 100 pc of four nearby starburst galaxies dominated both by photo dissociation regions (M 82) and large-scale shocks (NGC 253, IC 342 and Maffei 2), and to relate the chemical and physical properties of the molecular clouds with the evolutionary stage of the nuclear starbursts. Methods. We have carried out multi-transitional observations and analyses of three dense gas molecular tracers, CS, HC 3 N (cyanoacetylene) and CH 3 CC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
79
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(97 citation statements)
references
References 61 publications
17
79
1
Order By: Relevance
“…This could be explained if the gas in NGC 253 had a higher kinetic temperature. It seems that in these two galaxies, the spatial distribution of CS is similar to that of ammonia, or at least, is clumpier than those of H 2 CO and CO (Aladro et al 2011). If so, the kinetic temperature in M 82 would be around 60 K, while that of NGC 253 would be between 100 and 120 K. In that case, NGC 253 does not necessarily need to have higher H 2 densities than M 82, as seen by the LVG modelling of the CS emission towards these two galaxies by Aladro et al (2011).…”
Section: Comparison Of the M 82 And Ngc 253 Chemistriesmentioning
confidence: 86%
See 2 more Smart Citations
“…This could be explained if the gas in NGC 253 had a higher kinetic temperature. It seems that in these two galaxies, the spatial distribution of CS is similar to that of ammonia, or at least, is clumpier than those of H 2 CO and CO (Aladro et al 2011). If so, the kinetic temperature in M 82 would be around 60 K, while that of NGC 253 would be between 100 and 120 K. In that case, NGC 253 does not necessarily need to have higher H 2 densities than M 82, as seen by the LVG modelling of the CS emission towards these two galaxies by Aladro et al (2011).…”
Section: Comparison Of the M 82 And Ngc 253 Chemistriesmentioning
confidence: 86%
“…6). That HC 3 N has a very warm T rot in NGC 253 (73 K) seems to be related to the higher kinetic temperature of this galaxy, since the averaged n H 2 densities are lower in NGC 253 than in M 82 (Aladro et al 2011). The [c-C 3 H 2 /HC 3 N] ratio appears to indicate the evolutionary stage of the bursts of star formation (Fuente et al 2005).…”
Section: Comparison Of the M 82 And Ngc 253 Chemistriesmentioning
confidence: 87%
See 1 more Smart Citation
“…Though a small abundance difference of up to a factor of two may be claimed as is suggested by the observed difference in the low-J transition ratio (Aladro et al 2013), the larger difference observed in the high-J ratio is likely due to the excitation of CS. In starburst galaxies, the high-J transitions of CS appear to be associated to a moderately higher excitation temperature gas component (∼15-30 K, Aladro et al 2011b). This component appears to correspond to a dense molecular component (∼10 6 cm −3 ).…”
Section: The Hcn/cs Diagnosticmentioning
confidence: 93%
“…Though the assumption on the excitation temperature will not strongly affect the relative abundances given that most of our observed transitions have similarly low (4−10 K) energies, it might be an issue for the transition of HC 3 N with a significantly higher upper energy level (Table 1). However, the work by Aladro et al (2011b) toward nearby starbursts shows that such subthermal excitation affects equally to other molecular species in their lower J transitions, to those not only at lower energies but also up to transitions with ∼50 K upper energy levels. Additionally the non detection of the two higher energy transitions of HNCO listed in Table 1 and shown in Fig.…”
Section: Excitation and Column Density Determinationmentioning
confidence: 99%